How followers’ perception of followership prototype–traits fit impacts their job performance: a moderated polynomial regression analysis - Jing Yu; Jing Yu; Jian Feng (Frontiers in Psychology, 2024)
IntroductionPrevious studies about the drivers of follower performance focused on leadership, and most followership studies have used a single perspective to investigate this topic from the followers’ lens. Therefore, the purpose of this study is to explore whether, how, and when followers’ perception of followership prototype–traits fit influences their job performance.MethodsThe study adopted a questionnaire survey (Study 1) and a scenario experiment (Study 2). First, in the questionnaire survey, we collected 72 leaders and 262 followers from 72 teams of 14 companies in China using a two–wave research design. Second, in the scenario experiment, we invited 160 undergraduates from a university in southwest China to participate in the experiment after verifying the effectiveness of the manipulated materials.Results(1) compared with the misfit, followership prototype–traits fit is more likely to stimulate followers’ taking charge; (2) compared with low levels of fit, high-level followership prototype–traits fit is more likely to stimulate followers’ taking charge; (3) compared with high followership prototype and low followership traits condition, low followership prototype and high followership traits condition is more likely to stimulate followers’ taking charge; (4) followers’ taking charge mediates the impact of the followership prototype–traits fit on followers’ job performance; and (5) the impact of followership prototype–traits fit on followers’ taking charge is more salient for male followers than for female followers.DiscussionThis study not only helps capture the bidirectional and complex process of the interaction between leaders and followers during the followership, but also obtains a more comprehensive understanding of how this interaction affects followers’ behaviors and performance. The results have practical implications for improving followers’ job performance by highlighting the effects of followership prototype–traits fit on followers’ behaviors and performance.